INFLUENCE OF TECHNOLOGICAL FACTORS OF PRODUCING KNITWEAR FROM HIGH-STRENGTH THREADS ON THE LOOPS FORM AND STRUCTURAL PARAMETERS - ДМИТРИК, О. М.; ГАЛАВСЬКА, Л. Є. (Technologies and Engineering, 2024)
Purpose. By implementing an active experiment and establishing one-factor regression models, determine the influence of the type of raw material of increased strength, knitting density on the parameters of the structure and the formation of loops of knitted material produced on a gloves knitting machine from high-molecular weight polyethylene and para-aramid threads. Methodology. The work uses the basics of textile material science and the theory of knitting, methods of analysis and generalization of the obtained results. To determine the parameters of the structure of the knitted materials obtained, experimental methods of research using standard methods were used. Processing of the results of the experiment and construction of graphs was performed with the help of the Microsoft Excel program based on the average values of the indicators. In the research process, the method of linear regression analysis was used by the traditional planning of an active experiment. Results. To ensure the normal course of the knitting process when producing knitted material on the PA-8-33 8 gauge gloves knitting machine from 44texx3high-molecular weight polyethylene and para-aramid threads, the minimum and maximum leveles of sinking depth were set, namely for polyethylene thread hmin=3.55, hmax = 3.95 mm; for para-aramid thread hmin=3.4, hmax=3.8mm. Through the implementation of an active experiment on the gloves knitting machine, experimental samples of knitted material of a tubular shape were produced byplain interlooping from the high-strength threads at 5 levels of the sinking depth in a specified range with 0.1 mm step of, under the condition of constant tension of thread during the knitting process. During the research, the structural parameters and characteristics of the loops` shape of the obtained knitted materials were determined. Scientific novelty. On the flat knitting equipment equipped with sinkers, the nature of the influence of the change in the knitting density of the knitted material of the plain interlooping from high-molecular -weight polyethylene and para-aramid threads on the structural parameters and the loops formation was established. Practical significance. The obtained regression dependences allow, at the stage of designing the knitted material of plain interlooping, produced on a gloves knitting machine from high-molecular -weight polyethylene and para-aramid threads, to determine the structural characteristics and the loops shape as well to use these data to create the 3D models in computer simulation modeling and forecasting properties.